A STUDY REVIEW OF ACTIVE LEARNING STRATEGY IN IMPROVING STUDENTS' LEARNING MOTIVATION - Ubabuddin (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2020)
Scope: Learning approaches that are considered effective and feasible to be applied in the current learning process are active learning strategies. By using an active learning strategy, students will be invited to always be involved and motivated to do their best in each learning process, so that students will become excited in participating in learning. Objective: This qualitative study presented the results of literature reviewed gathering from various theories, including national, international journals, books, internet and other literature to answer the problem formulation. Method: A serial of literature on active learning strategies that actively applied in most modern education were reviewed and presented to answer the research question. Findings: based on many experts in the fields of teaching and learning, the findings of this study were First, Active learning starts with questions, card short, the power of two, jigsaw, Index card match, picture and picture, cooperative script, problem based instruction, students team achievement devision, etc. Significance: The findings of this literature rewiewing has promoted students better thoughtful and understanding on material presented as participants engaging themselves with the lesson cores not simply just follow teacher's instruction. These findings are also so useful insight to keep student's concentration and improving learning achieving to the higher learning outcomes as demanded by instructional curriculum. Recomendation: Monotonous and teacher-focused learning is increasingly in demand and continues to be abandoned because it makes students bored and boring. With an effective approach it is hoped that learning objectives can be optimally achieved.